Marine and Coastal Resources Governance Issues in Casamance, Senegal: Example of MPAs - Soda Loum; Mamadou Thior; Issa Sakho; Michel Desse (European Scientific Journal, ESJ, 2022)
The maritime zone of Casamance (south of Senegal), like everywhere in the West African coast, has become a competitive area for development projects. This competition appears in different forms and affects several sectors (fishing, tourism, real property, mining, etc.). These different actors have developed forms of competition that are poorly circumscribed by public policies, thus leading the State of Senegal to resort to Marine Protected Areas (MPAs). The governance of Marine Protected Areas has also become a trend due to its participatory approach which highlights the common desire to preserve marine and costal natural resources. The framework of the participatory governance has organisational and legal limitations that require corrections sometimes in order to become more effective and efficient. This paper focuses on the role of protected areas in the regulation of tensions around marine and coastal resources in Casamance. The approach is based on the review of documents (scientific and strategic policies, etc.) and field training on the protected areas of Casamance. The results indicate that the MPAs are an excellent governance strategy and have led to better conservation of marine and coastal resources in Casamance.